2002
DOI: 10.3354/meps237027
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of iodate to iodide in marine phytoplankton cultures

Abstract: Six species of phytoplankton, representing 6 major phylogenetic groups (2 oceanic species: a cyanobacteria, Synechococcus sp., and a coccolithophorid, Emiliania huxleyi; and 4 coastal species: a prasinophyte, Tetraselmis sp., the green algae Dunaliella tertiolecta, the diatom Skeletonema costatum and a dinoflagellate Amphidinium carterae) were tested for their ability to reduce iodate to iodide in batch cultures. They all did so to varying degrees. Thus, the reduction of iodate to iodide by phytoplankton may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 54 publications
9
64
1
1
Order By: Relevance
“…Our findings apparently contradict the earlier work of Wong et al (2002), who found no clear relationship between iodide production and the growth phase of the culture. Indeed, they ruled out cell lysis as a possible cause, though this may have been because they did not measure cell numbers or any proxy of cell permeability.…”
Section: The Role Of Cell Permeabilitycontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings apparently contradict the earlier work of Wong et al (2002), who found no clear relationship between iodide production and the growth phase of the culture. Indeed, they ruled out cell lysis as a possible cause, though this may have been because they did not measure cell numbers or any proxy of cell permeability.…”
Section: The Role Of Cell Permeabilitycontrasting
confidence: 99%
“…Average production rates per day were in agreement with those reported in previous studies (Wong et al 2002) and are shown in Table 3. In all cultures, except Scrippsiella trochoidea, the iodide production began in the stationary growth phase (Figs.…”
Section: Iodide Production Rates (K) Per Daysupporting
confidence: 91%
See 3 more Smart Citations